2021
DOI: 10.1088/1755-1315/719/4/042073
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for Vertical Bearing Capacity Calculation of Rock-Socketed Piles in Karst Area Based on Load Transfer Method

Abstract: Due to the complex geological conditions and many influencing factors in karst areas, this paper conducted theoretical, experimental research and calculation analysis on the design and construction of engineering piles of bridge engineering in karst cave areas. An algorithm for vertical capacity calculation of rock-socketed piles in karst area based on load transfer method was developed. The results using this new method were analyzed and compared with the results from the static load test of three engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…For instance, Huang et al [ 7 ] introduced a novel theoretical model for a large-diameter stepped-tapered hollow pile, addressing the issue of instability in the bearing layer due to karst geological conditions. He et al [ 8 ] established models to calculate the side resistance, frictional resistance, and pile-end resistance of rock-socketed piles in the karst area. Xing et al [ 9 ] assessed the impact of various pile driving techniques and grouting methods on the mechanical properties of rock-socketed piles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Huang et al [ 7 ] introduced a novel theoretical model for a large-diameter stepped-tapered hollow pile, addressing the issue of instability in the bearing layer due to karst geological conditions. He et al [ 8 ] established models to calculate the side resistance, frictional resistance, and pile-end resistance of rock-socketed piles in the karst area. Xing et al [ 9 ] assessed the impact of various pile driving techniques and grouting methods on the mechanical properties of rock-socketed piles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Suloshini et al carried out a pile resistance test of bored pile in intact rock and found that pile lateral friction remained unchanged when the confining pressure ranged from 0 kPa to 400 kPa [22]. Based on the theoretical and experimental analysis of the load transfer law of rock-socketed piles in a Karst region, He et al proposed a calculation method for the vertical bearing capacity of rock-socketed piles in a Karst region based on the load transfer method [23]. Wang et al studied the load transfer mechanism of rock-socketed piles and found that pile side friction is related to the mechanical properties of the soil beside the pile [24].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al divided the entire settlement process into three parts after analyzing the axial load-settlement law of bored piles containing debris [20]. Using static load testing of pile foundations in karst areas, He et al proposed a method for calculating the vertical bearing capacity of pile foundations based on the load-transfer method [21]. A method to determine the critical load for pile buckling when navigating a single-level cavern was put forth by Lei et al after conducting indoor model experiments [22].…”
Section: Introductionmentioning
confidence: 99%